Identificación de las medidas de control para los impactos ambientales establecidos durante el cultivo de cacao en el municipio de rivera del departamento del Huila - Rico Florez, Andrei Hassib; Perdomo Ardila, Brayan Humberto (Universidad Antonio Nariño, 2021)
This project aims to identify and define the environmental aspects and impacts, positive and negative, of the production of cocoa in the municipality of Rivera, in the department of Huila, as a contribution to improve the management of the crop and optimize the use of resources in friendly composition with the environment. From this point of view, our contribution to this sector will be the identification of environmental aspects and impacts that can be generated by the development in the production of cocoa, for this to close even more the productive cycle improving it from all the points of view, generating added value and encouraging the development of the sector.